Findings of the Association for Computational Linguistics: EMNLP 2020 2020
DOI: 10.18653/v1/2020.findings-emnlp.261
|View full text |Cite
|
Sign up to set email alerts
|

LEGAL-BERT: The Muppets straight out of Law School

Abstract: BERT has achieved impressive performance in several NLP tasks. However, there has been limited investigation on its adaptation guidelines in specialised domains. Here we focus on the legal domain, where we explore several approaches for applying BERT models to downstream legal tasks, evaluating on multiple datasets. Our findings indicate that the previous guidelines for pre-training and finetuning, often blindly followed, do not always generalize well in the legal domain. Thus we propose a systematic investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
118
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(184 citation statements)
references
References 19 publications
(17 reference statements)
1
118
1
4
Order By: Relevance
“…This evidence comes from the court's own guidelines (ECtHR, 2014), but can also be found in the writings of a former judge of the ECtHR (Zupancic, 2016) and of legal scholars (Lupu and Voeten, 2010). Second, there is existing research on the neural modeling of ECtHR case law we can build upon (Aletras et al, 2016;Chalkidis et al, 2019Chalkidis et al, , 2020. Third, the documents of the ECtHR case law, unlike those of most other courts, textually separate the facts from the arguments, which is crucial for our experiments.…”
Section: K K=1 P(o K | •)mentioning
confidence: 99%
“…This evidence comes from the court's own guidelines (ECtHR, 2014), but can also be found in the writings of a former judge of the ECtHR (Zupancic, 2016) and of legal scholars (Lupu and Voeten, 2010). Second, there is existing research on the neural modeling of ECtHR case law we can build upon (Aletras et al, 2016;Chalkidis et al, 2019Chalkidis et al, , 2020. Third, the documents of the ECtHR case law, unlike those of most other courts, textually separate the facts from the arguments, which is crucial for our experiments.…”
Section: K K=1 P(o K | •)mentioning
confidence: 99%
“…The BERT language model (Devlin et al, 2019) has been shown to be effective on a wide range of tasks in the legal domain, including Named Entity Recognition (Chalkidis et al, 2020), annotation of legal concepts (Chalkidis et al, 2020), and evidence retrieval (Soleimani et al, 2020).…”
Section: Approachmentioning
confidence: 99%
“…SciBERT took 7 days to train from scratch with a single TPU v3 with 3 cores [9]. In [18], a legal language model, LEGAL-BERT, is trained on a 12 GB corpus of legal texts, either from scratch or further pre-trained from BERT-Base. The authors found that both were valid approaches with similar results.…”
Section: B Domain-specific Language Modelsmentioning
confidence: 99%
“…The authors found that both were valid approaches with similar results. Our training corpus has a similar size as [18] and we use a single NVIDIA V100 GPU with 16 cores to train our models. Based on these limitations, the decision was taken to further pre-train our domain-specific models rather than train them from scratch.The methods mentioned in this Literature Review are summarised in Table 1.…”
Section: B Domain-specific Language Modelsmentioning
confidence: 99%